Spray drying of Ati-ati plant boiling extract - Siti Aisyah, Yahya (2010)
In this work, optimization and scale up of the spray drying ati-ati plant boiling extract was studied. The variables that influence the antioxidant activity of ati-ati plant are studied and determined. In this research spray drying has been adopted to produce the dried extract from the liquid form of the boiling extract of ati-ati plant. Analysis on the dried extracts has been conducted using an antioxidant assay are based on measurement of the loss DPPH color at 517 nm after reaction with test compound and the reaction is monitored by UV-VIS spectrophotometer. The 22 factorial experiment method is used to design the experiment around a centre point of temperature and concentration of maltodextrin which gave the optimum antioxidant activity at small scale. Among the experimental points, the highest yield of antioxidant activity is produced in condition of 150 oC and 10% concentration of maltodextrin. This experiment was followed by mathematical analysis using Yates’ method and linear regression in order to study the main effect and interactive effect of changing the level of experimental variables. The calculation proved that concentration of maltodextrin has the biggest main effect on antioxidant activity while the interactive effect of the combination of temperature and concentration of maltodextrin is also significance. The 22 factorial experiments were complemented with more experiments to make a composite design in order to determine the maximum point. The maximum predicted yields according to the optimized levels of variables are 57.3427% of antioxidant activity at temperature of 165.26oC and 19.35% concentration of maltodextrin.